STUDENT LED DEVELOPMENT AND EVALUATION OF UNDERGRADUATE NEUROLOGY VIRTUAL PATIENT E-LEARNING MODULES. (29th November 2012) - Phizacklea, J; Koecher, S; Kobialka, K; Davis, G; Cossburn, M
Abstract : Background: Long-term neurological conditions causing disability affect up to 8 million people in the UK, yet are often neglected by medical school curricula. Aim: A student led project to develop e-learning modules on traumatic brain injury, spinal cord injury, motor-neurone disease and secondary progressive multiple sclerosis. The students aimed to create accurate, up-to-date and cognitively engaging learning resources for medical students. Methods: During a multi-step process, students conducted literature researches, spent time with patients and specialists and considered current guidelines when constructing the virtual patient e-modules. Pilots were assessed by medical students in 4th and 5th year. Volunteers completed pre and post-module questionnaires and feedback forms. Results: The difference between pre- and post-module scores showed mean improvements of between 30.4% and 40.8% overall (p<0.001). Feedback revealed >90% satisfaction with the learning experience. Conclusions: The e-modules were well received by students who felt the material was specific to their learning needs. Many participants felt more appreciative of the difficulties these patients face, and more confident in managing these important conditions. Feedback from students was used to improve the final e-modules. Results suggested that it could be beneficial for more resources to be invested in the development of student led e-learning modules, based on clinical experiences, in the future.